The Impact of Philosophical Literary Stories in the Development of Creativity in Relation to Nature Protection and Sustainable Development - Borisová, Simona; Pintes, Gábor (Journal of Education Culture and Society, 2023)
Aim. The paper is focused on the area of philosophical literary stories included in the educational programme Philosophy for Children. The paper aims to identify, reflect and analyse the categories of creative thinking in such stories. Methods. The main method through which we deal with categories of creative thinking is represented by the interpretation of the literary text in several philosophical stories. An additional method is the analysis of documents – individual books containing philosophical literary stories. Results. The analysis of several stories shows that creative thinking in philosophical literary stories is identified in the categories of imagination, applicability, originality, surprise, experimentation, encouragement of the creativity of others and imaginativeness. The major characters are using original solutions to problems, they are able to apply the solved problem to a new situation, ask questions and their thought processes are often surprising. Problematic to determine is the category of imagination, with which the character can think about a possible world or problem solving. Conclusion. In contrast to the classical aesthetic literary text, this specific type of text brings the reader model solutions to many problems of everyday life. The focus of the Philosophy for Children can also aim at ecological and environmental issues and individual participants in the community of inquiry are thus encouraged to stimulate their creativity in the field of nature protection and sustainable development from an early age.